THE HUNGER GAMES: REPRESENTING THE NEW IMAGE OF AMERICAN POPULAR HEROES - Aidatul Chusna; Lynda Susana W.A.F. (Celt: A Journal of Culture, English Language Teaching & Literature, 2015)
This research is aimed at revealing the new image of American popular heroes as depicted in the novel adaptation film of The Hunger Games which is created as a trilogy, which consists of two more novels: Catching Fire and Mockingjay. This film is one of the most phenomenal films in 2013-2104, which grossed out up to $407,999,255. This research used textual approach, which focused on the text as the object, that is The Hunger Games film. The result shows that The Hunger Games essentially brings the issue of slavery back into scrutiny. However, the creation of the heroin in the film is granted as the reconstruction of popular heroes in America. She is an inspiring female hero which is exemplified as the appreciation of womens values. Yet, the heroin is broadly defined with the qualities of rouge heroes as the characteristics are the representation of the belief and values associated with freedom to wash away the oppression restore the rights of the minority. In addition to the issue of slavery , the symbols of new hope and new spirit are implicitly emerged in the story. This attempt was proficiently done by the heroin, which was eventually created as the new image of the American heroes.